Harry W. Frantz papers - Frantz, Harry W. (Harry Warner), 1891-1982.
Scrapbooks (1923-1954) containing correspondence, book jackets, newspaper clippings, magazine articles, pamphlets, and photographs; and printed matter including monographs, pamphlets, reports, schedules, magazines, and publicity and other material. The collection relates to aviation, the field Frantz covered as a correspondent for United Press International. Topics include pioneering long distance and endurance flights and the early history of Pan American Airways and other commercial passenger and freight air carriers. Includes "Dear Senor" letters, newsletters written to journalists by Pan American Airways Corporation publicity director William Van Dusen. Correspondents include Arthur E. Curtis, Roy Wilson Howard, Manuel DeJ. Manduley, and B.V. McCandlish.
Library of Congress Geography and Map Division.
Journalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Curtis, Arthur E. -- Correspondence; Howard, Roy Wilson, -- 1883-1964 -- Correspondence; Manduley, Manuel DeJ. -- Correspondence; McCandlish, B. V. -- 1886-1975 -- Correspondence; Van Dusen, William, -- 1901-1976.; Pan American Airways Corporation; United Press International; Aeronautics -- Flights; Aeronautics -- History; Aeronautics, Commercial; Airlines; Endurance flights; Journalism, Aeronautical; Airlines -- Public relations; Journalists